The Fabrication Of Porous Ceramic - Muhammad Syamil, Junid (UTeM, 2008)
Porous ceramics are desirable for certain application like filters, humidity and gas sensors. Porosity can be found in almost every types of materials science like -metals, ceramics, polymers, composites, semiconductors and biomaterials.The best well known porous materials is ceramics. In order to produce porous ceramic some special technique will be implemented during the process. Some amount of charcoal will be mix up in the mixture prior sintering and will be burned out to leave the pores at sintering temperature of l250°C. There are 8 different sample produces which have charcoal wt% as these, 0 wt%, l wt%, 2 wt%, 3 wfl/o, 4 wt%, 5 wt%, 6 wt%, and 7 wt% respectively. lt was found that it was proved the more weight percentage (wt %) charcoal was added the porosity distribution also would increase. The SEM microstructure could describe briefly the distribution of the porosity inside those pallets and the average size of pores. There were also several standard testing procedures successfully conducted for porous ceramic to determine characteristics, properties and behaviors. The diameters, weight distribution, relative density after sintering (gmm"3 ), and the Vickers Hardness value after sintering were directly proportional to the charcoal wt% composition added. The relative volume and porosity volume were calculated to detennine exact porosity.